A New Contract? The Joint Mobilization of Unionized and Contract Workers in Latin America. (May 2022) - Holland, Alisha C.
ABSTRACT: Comparative political economists often divide Latin American labor markets into those with secure employment (insiders) and those without it (outsiders). Yet this division misses an increasingly important class of contract workers, who hold formal labor contracts but often lack labor stability, welfare benefits, and organizing rights. When do unionized and contract workers share preferences and engage in joint organizing? And when do their efforts result in policy change? Drawing on case studies of Chile and Peru, I argue that unionized workers mobilize contract workers when they see their own membership under threat and when they share physical workplaces with contractors. Labor coalitions succeed in policy reform when they leverage divisions within the business community and upcoming elections to build support. This article thus pushes scholars to move beyond dichotomies of formal versus informal workers and study how contract workers matter for collective action and labor policy outcomes.